Macro BIM Adoption Study in Peru - Murguía Sánchez, Danny (Pontificia Universidad Católica del Perú. Departamento de Ingeniería, 2019)
The “First Macro BIM Adoption Study in Peru” is the result of a collaboration between the BIMe Initiative and the School of Engineering of the Pontifical Catholic University of Peru. The findings of this report are intended to assist policymakers in defining policies, strategies, and plans for the diffusion of BIM at a market scale. From the BIMe Initiative, the project is led by Dr Bilal Succar of Change Agents, Australia, and Dr Mohamad Kassem of Northumbria University, United Kingdom. From the Pontifical Catholic University of Peru, the project is led by Danny Murguía. More information about the BIMe Initiative Macro Adoption Project can be found at https://bimexcellence.org/projects/macro-adoption/
2019 Macro BIM adoption study in Peru
Keywords: Bime Initiative; Building Information Modelling (BIM); Technology developers; Policy makers; Educational institutions; http://purl.org/pe-repo/ocde/ford#2.00.00